Narrative paradigms of sustainability in the law practice. The challenge of progress in the Computational Court-Environment (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
By the relationship between the idea and the science of sustainability, the paper is all about the evolution of a paradigm that encloses the law practice. As the notion of environment is the main referent of the study on sustainability, as the system of the administration of justice becomes a virtual environment for the application of the idea of sustainability. Based on the concept of progress the robotic judicial decision, a reflection of algorithmised law practice, is an opportunity to verify what implications can be arise from the transdisciplinary and methodological growth of the science of sustainability.
Keywords: Sustainability; progress; ethics; court-environment